Efektivitas Pendidikan Pancasila Bagi Generasi Z Dalam Mencegah Disintegrasi Sosial Di Era Digitalisasi - Agus Tina Wulandari; Sarah Angelina Panggabean; Furqon Mubarok; Herli Antoni (Pusat Riset dan Inovasi Nasional, 2025)
Pancasila education has a strategic role in shaping the character of the younger generation, especially generation Z, during the challenges of globalization and the development of the digital era. This study aims to analyze the effectiveness of Pancasila Education in preventing social disintegration that is increasingly rampant due to shifting values, individualism, and social fragmentation. Using a qualitative approach, this study explores the implementation of Pancasila values in the life of generation Z through formal education curriculum and non-formal activities. The results of the study show that the understanding and internalization of Pancasila values can increase collective awareness, social solidarity, and tolerance in the face of diversity. However, challenges in the form of lack of innovation in teaching methods and low active participation of generation Z are obstacles that need to be overcome. Therefore, strengthening Pancasila Education with a relevant and adaptive approach to the needs of generation Z is urgently needed to prevent social disintegration in the digital era.